(untitled) (INTERNATIONAL SEMINAR, 2025)
This study aims to analyze the application of the principle of duty of care in medical practice and its implications for physician negligence in Indonesia. The method used is normative with a juridical and conceptual approach, reviewing regulations, medical codes of ethics, literature, and court decisions through literature studies. Data were analyzed qualitatively to interpret the relationship between professional standards, duty of care, and legal liability for negligence in medical practice. The results of the study show that the principle of duty of care is the main guideline in determining whether a doctor’s action falls into the category of negligence or is still a reasonable professional judgment. The application of this principle requires that every medical procedure be carried out carefully in accordance with operational standards of procedures and full awareness of the potential risks that exist. Violations of principles such as misdiagnosis, improper treatment, and ineffective communication to patients can be considered negligence and have the potential to give rise to civil, criminal, or administrative liability. Factors that affect physician compliance include understanding of regulations and ethics, competence, condition of health facilities, effective communication, and professional supervision. Efforts to prevent medical negligence based on the obligation to be cautious include continuous training, implementation of SOPs, use of information technology, professional supervision, and active patient participation so that health services can be carried out safely, professionally, and reliably.